2015
DOI: 10.1007/s00464-015-4674-z
|View full text |Cite
|
Sign up to set email alerts
|

Resident involvement in laparoscopic procedures does not worsen clinical outcomes but may increase operative times and length of hospital stay

Abstract: We demonstrate resident involvement is safe and does not result in poorer patient outcomes. Readmissions and LOS were higher in BL, and operative times were longer in all surgeries. Resident operations do appear to have real consequences for patients and may impact the healthcare system financially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…The authors stated in their conclusion, ''Resident operations do appear to have real consequences for patients and may impact the healthcare system financially.'' 18 Clearly the end result of an operation (ie, the composite TPS) is important, but our results would support the contention that the time it takes to achieve a given result and the number of tries necessary should also be considered. Unfortunately, given the limited number of surgeons in this series, we were unable to look at the influence of surgeon experience on outcome, but would expect that there would be an inverse relationship, as demonstrated in prior studies.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The authors stated in their conclusion, ''Resident operations do appear to have real consequences for patients and may impact the healthcare system financially.'' 18 Clearly the end result of an operation (ie, the composite TPS) is important, but our results would support the contention that the time it takes to achieve a given result and the number of tries necessary should also be considered. Unfortunately, given the limited number of surgeons in this series, we were unable to look at the influence of surgeon experience on outcome, but would expect that there would be an inverse relationship, as demonstrated in prior studies.…”
Section: Discussionmentioning
confidence: 57%
“…15 Related surgical disciplines use operative time in a parallel fashion, and decreases in task time are often used to demonstrate improved learner skill and proficiency. 16,17 Moreover, Jolley and colleagues 18 have shown that increased operative times, which were found in cases performed by less-experienced surgeons, increased resource use. The authors stated in their conclusion, ''Resident operations do appear to have real consequences for patients and may impact the healthcare system financially.''…”
Section: Discussionmentioning
confidence: 99%
“…We consider this increase to be economically justifiable in the context of surgical training at a university hospital. Jolly examined the effect of resident participation in basic and advanced laparoscopic surgery and demonstrated an increase in the length of stay, especially for more complex procedures [22]. However, that study suffers from the limitations of most American College of Surgeons NSQIP database analyses, as it offers no information about the degree of resident involvement.…”
Section: Discussionmentioning
confidence: 96%
“…LA has been widely accepted as a parameter to use in evaluating the effectiveness of education and training for surgical residents. First of all, resident involvement did not increase the level of risk to patients, despite past controversy [11][12][13][26][27][28]. Similarly, a comparison of the outcomes between residents and staff surgeons suggested that LA as performed by residents was generally safe (Table 4).…”
Section: Discussionmentioning
confidence: 97%
“…Several reports have already highlighted LA as a viable assess-ment of education for surgical residents. Among them were reports showing that surgery performed by residents resulted in similar clinical outcomes as those following surgery conducted by attending or supervising surgeons [11][12][13]. Others have sought to delineate the learning curve (LC) for LA performed by residents [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%